2022
DOI: 10.1038/s41598-022-16064-y
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady MHD free convection flow of an exothermic fluid in a convectively heated vertical channel filled with porous medium

Abstract: Utilizing porous media in a new mathematical model to improve convective heat transfer characteristics in a variety of applications, such as radiation nuclear disposal storing, evaporation cooling, sieving, geological extraction, crude petroleum refining, and building heating and cooling, is becoming increasingly important. This study proposed a numerical analysis of the unsteady magnetohydrodynamic free convection flow of an exothermic fluid with Newtonian heating. This discovery reveals two types of solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…During the computation, the chemical reaction parameter, chemical kinetic exponent, thermal Biot number, porous medium, and Navier slip parameter were shown to be highly reliant on the spike in momentum and energy profile. Similarly, it was demonstrated throughout the computational process that increasing MHD increases the thickness of the momentum boundary layer, resulting in a dropin fluid velocity following Hamza et al [6]. From a physical standpoint, M = 0 signifies no magnetic impact, and the flow is entirely hydrodynamic.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…During the computation, the chemical reaction parameter, chemical kinetic exponent, thermal Biot number, porous medium, and Navier slip parameter were shown to be highly reliant on the spike in momentum and energy profile. Similarly, it was demonstrated throughout the computational process that increasing MHD increases the thickness of the momentum boundary layer, resulting in a dropin fluid velocity following Hamza et al [6]. From a physical standpoint, M = 0 signifies no magnetic impact, and the flow is entirely hydrodynamic.…”
Section: Discussionmentioning
confidence: 80%
“…An alternative study was also conducted on unsteady MHD free convective flow in a vertical tube covered with absorbent material [5].Porous media are sometimes employed in a unique computational framework to increase convective heat transfer properties for someutilizations, including radioactive waste storage, transpiration cooling, crude oil refining, and building heating and cooling. Hamza and colleagues [6] investigated MHD-free convection flow in a vertical plate embedded with porous material. They identified that porous media had a major impact on fluid flow.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effect of various parameters on fluid velocity is presented graphically, and the time of steady state has been evaluated. The studies [11][12][13][14] presented unsteady flow and heat transfer of a viscous, incompressible electrically conducting fluid through a porous horizontal channel. The associated equations of the problem were transformed to dimensionless form and treated analytically using the perturbation method.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent work, Hamza et al (2023) used homotopy perturbation method to explore the characteristics of Arrheniuscontrolled heat transfer fluid on free convection affected by an induced magnetic field. Later, Hamza et al (2022) evaluated the convectively heated, MHD-free flow of a chemically reacting fluid in a vertical channel contemplated with porous media. The steady-state component was solved using the homotopy perturbation method while the unsteady state case was analyzed using a numerical technique.…”
Section: Introductionmentioning
confidence: 99%